UJI AKTIVITAS ANTIDIABETES EKSTRAK ETANOL BIJI BUAH PARE (Momordica Charantia) PADA MENCIT (Mus Musculus) - Devitria, Rosa; Elfia, Mega; Yesti, Yulia; Rafa, Huda Nur (Ensiklopedia of Journal, 2024)
Diabetes Mellitus (DM) is defined as a disease or chronic metabolic disorder with multiple etiologies characterized by high blood sugar levels accompanied by disturbances in carbohydrate, lipid and protein metabolism as a result of insulin insufficiency. The use of traditional medicine in Indonesia is currently in great demand by the public, one type of plant that is widely used as traditional medicine is bitter melon (Momordica charantia). The ingredients of bitter melon which are useful for lowering blood glucose are charantin, insulin polypeptide-P, and lectins. This study aims to determine the antidiabetic activity of the ethanol extract of bitter melon seeds (Momordica charantia) against male mice (Mus musculus) charged with 50% glucose solution. Tests for antidiabetic activity in mice were carried out in 5 treatment groups, namely the negative control group (1% w/v Na-CMC), the positive control group (0.01% Glibenclamide suspension), the first test group (50 mg/kg BW of bitter melon seed extract). , Test Group II (150 mg/kgBB ethanol extract of bitter melon seeds), and Test Group III (250 mg/kgBB ethanol extract of bitter melon seeds). The results of the study were analyzed using the One-Way ANOVA statistical test. The results showed that the ethanol extract of bitter gourd seeds was able to inhibit glucose absorption where the greatest total inhibition occurred at a dose of 250 mg/kg, namely 118 mg/dL, then at a dose of 150 mg/kg, namely 88 mg/dL, and finally at a dose of 50 mg/kg, which is 116 mg/dL.Keywords: Bitter melon fruit seeds (Momordica charantia), antidiabetic, male mice (Mus musculus)